Explaining Job Satisfaction Among Residents in Standardized Residency Training Programs: A Serial Multiple Mediation Model - Zhang H; Chen D; Cui N; Zou P; Shao J; Wang X; Zhang Y; Du J; Du C; Zhou G; Zheng D (Dove Medical Press, 2021)
Hui Zhang1 *, Dandan Chen2 *, Nianqi Cui,3 Ping Zou,4 Jing Shao,2 Xiyi Wang,5 Yichi Zhang,6 Jiao Du,6 Chunxue Du,6 Guanglan Zhou,6 Deyi Zheng6 1Department of Cardiology, Guizhou Provincial People's Hospital, Guiyang, People's Republic of China; 2Zhejiang University School of Medicine, Sir Run Run Shaw Hospital, Hangzhou, People's Republic of China; 3The Second Affiliated Hospital Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 4School of Nursing, Nipissing University, Toronto, Ontario, Canada; 5Shanghai JiaoTong University, School of Nursing, Shanghai, People's Republic of China; 6Department of Burn and Plastic Surgery, Guizhou Provincial People's Hospital, Guiyang, People's Republic of China*These authors contributed equally to this workCorrespondence: Deyi ZhengDepartment of Burn and Plastic Surgery, Guizhou Provincial People's Hospital, Guiyang, People's Republic of ChinaTel +86 13984826262Email deyizheng@126.comBackground: Despite a flood of research on job satisfaction, few studies have examined how and why social support influences job satisfaction. This study aimed to explore how social support has an indirect effect on job satisfaction by examining its impact on emotional exhaustion and anxiety symptoms among residents of the physicians standardized residency training program in China.Methods: This cross-sectional study adopted questionnaires to collect data from residents in the standardized residency training program in China. The PROCESS macro for SPSS based on ordinary least-squares regression and the bootstrap method was used. The indirect effect of social support was examined using bootstrapping procedures. A serial multiple mediation model was examined in which social support was associated with job satisfaction via emotional exhaustion and anxiety symptoms.Results: There were 269 residents who provided usable data for the analysis. The mean age of residents was 25.98 years old. Close to half (52%) of the participants were female. The total indirect effect of social support on job satisfaction was significant (ab=0.21, SE=0.05, CI=0.12 to 0.32). The specific indirect effect 1 (social support→emotional exhaustion→job satisfaction) was significant (a1b1=0.12, SE=0.04, CI=0.05 to 0.19). The specific indirect effect 2 (social support→anxiety symptoms→job satisfaction) was significant (a2b2=0.07, SE=0.03, CI=0.02 to 0.13).The specific indirect effect 3 (social support→emotional exhaustion→anxiety symptoms→job satisfaction) was also found to be significant through both optimism and work engagement (a1a3b2=0.03, SE=0.01, CI=0.01 to 0.05).Conclusion: It seems critical for hospital management to develop a supportive work environment to improve the effects of emotional exhaustion and anxiety symptoms and to provide sufficient support to improve job satisfaction among residents in standardized residency training programs.Keywords: residents, social support, emotional exhaustion, job satisfaction, anxiety symptoms, standardized residency training programs